2000
DOI: 10.1097/00000539-200002000-00018
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Effects on Coagulation of Midtrimester and Final-Trimester Amniotic Fluid on Whole Blood by Thrombelastograph® Analysis

Abstract: We used the Thrombelastograph((R)) test (Haemoscope Corporation, Skokie, IL) to assess the effects of midtrimester and final-trimester amniotic fluid (AF) on whole blood coagulation. Results demonstrate that AF accelerates clot initiation and propagation. The Thrombelastograph((R)) test may be useful in assessing coagulopathy in patients with AF embolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
4
8
0
Order By: Relevance
“…Harnett et al, 78 using thromboelastography analysis, have demonstrated that the addition of amniotic fluid to blood from pregnant women causes a hypercoagulable state related to the procoagulant activity of amniotic fluid and enhanced platelet activation, but there was no evidence of fibrinolysis, suggesting that the primary cause of bleeding in AFE is consumption coagulopathy. Similar results were reported by Liu et al, 79 using blood from non pregnant women.…”
Section: Resultssupporting
confidence: 91%
“…Harnett et al, 78 using thromboelastography analysis, have demonstrated that the addition of amniotic fluid to blood from pregnant women causes a hypercoagulable state related to the procoagulant activity of amniotic fluid and enhanced platelet activation, but there was no evidence of fibrinolysis, suggesting that the primary cause of bleeding in AFE is consumption coagulopathy. Similar results were reported by Liu et al, 79 using blood from non pregnant women.…”
Section: Resultssupporting
confidence: 91%
“…This substantiates the hypothesis that coagulation profile changes are invariable accompaniments of AFE [106]. The Thrombelastograph1 test may therefore be useful in assessing coagulopathy during or after AFE [107]. AF also contains large amounts of tissue factor (TF) pathway inhibitor (TFPI), accounting for virtually all of its coagulant potential.…”
Section: Pathophysiologysupporting
confidence: 72%
“…This technology has been used extensively in the monitoring of hemostasis during major surgical interventions such as liver transplantations [9,10], cardiovascular procedures [11][12][13][14][15], trauma [16] and neurosurgery [17,18]. It has also been used in the management of obstetrical complications [19][20][21] and of deep vein thrombosis [22] as well as in the monitoring of antagonists of platelet GPIIb/IIIa [23,24], platelet thromboxane A 2 and ADP [25], and recombinant Factor VIIa [26,27]. Its use has resulted in reduction in the use of blood products [9][10][11][12]15] during surgery, and in the rate of re-exploration in cardiac surgery [15].…”
mentioning
confidence: 99%